The effect of varying levels of potassium hydroxide-treated false Yam seed meal on growth performance, haematology and serum biochemistry of male broiler chickens - Mohammed, Alhassan (Asia Pacific Network for Sustainable Agriculture, Food and Energy Network (SAFE Network), 2023)
This study was carried out to evaluate sequential treatment of false yam seeds as substitute for maize in broiler chicken diets on their growth, carcass, haematology and serum biochemistry. Ripped fruits of false yam plants growing in the wild were harvested by hand picking. The fruits were partially sun-dried to reduce their moisture content and facilitate cracking to obtain the false yam seeds (FYS). The fresh FYS were crushed with a stone to reduce size, increase surface area and facilitate processing. The freshly crushed false yam seeds were subjected to multiple-stage processing where seeds were first soaked in ordinary water (i.e., addition of fresh seeds in ordinary water at a ratio of 1:2, wt/vol) for 12 days with water being changed every 3 days. After the 12 days of soaking, the seed sample was washed with clean ordinary water. In the second stage of processing, soaked FYS was soaked in a solution of 1M concentration of potassium hydroxide at a ratio of 1:2 (wt/vol) for 24 hours, after which the sample was washed thoroughly with clean ordinary water. The last stage of processing involved blanching of potassium hydroxide-treated seeds, firstly by immersing the sample in hot water (900C) for 20 minutes and then transferring it into cold water (40C) for 40 minutes. The treated seed sample was then washed with clean water, sun-dried to approximately 12% moisture on a cement floor and ground into gritty flour using a hammer mill. The treated false yam seed meal was labeled as KOH_T FYSM. At 21 d of age, 128 birds were individually weighed and then randomly assigned to one of four dietary treatments in quadruplicate lots. Each replicate had 8 male broilers. The mean live-weight of birds in each replicate was 883 g (±0.05). The four treatments included the control without KOH_T FYSM; treatments 2, 3 and 4 contained 100, 300 and 500g/kg KOH_T FYSM respectively replacing maize (wt. /wt. basis) in a completely randomized design. The birds were fed various diets for 35 d. The growth response of male broiler chickens fed diets supplemented with varying levels of KOH_T FYSM revealed no significant (P<0.05) difference in all growth parameters measured. Carcass dress weight and carcass dressing showed no significant (P>0.05) difference at 500g/kg. However, the relative weight of organs revealed a significant (P<0.041) increase in the heart weight and a reduction in the weights of the liver and the spleen. Haematological parameters evaluated revealed a significant (P<0.05) decrease in the haemoglobin, mean corpuscular volume, mean corpuscular haemoglobin and mean corpuscular haemoglobin concentration as KOH_T FYSM was increased in the diets. The economics of replacing maize with KOH_T FYSM in the diets of male broilers revealed that price per kg of feed reduces as the test material was increased in the diets. Inclusion of KOH_T FYSM up to 500g/kg in the diets of male broilers had no adverse effect on their growth performance. However, its inclusion influenced internal organ weights such as the liver, spleen and heart. Economics of feeding KOH_T to broilers did not increase cost of feeding, suggesting that, There is an economic value for using this product for broiler chickens as an alternative to maize during periods of scarcity and can be recommended for use by farmers where this plant is available.